Rosuvastatin effects on systemic oxidative stress, endogenous inflammation and main neoangiogenesis factors in patients with atherosclerosis - Yu. V. Shchukin; E. I. Seleznev; V. A. Dyachkov; E. A. Medvedeva; E. A. Surkova; А. E. Ryabov (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To investigate rosuvastatin effects on oxidative stress (OS), endogenous inflammation and neoangiogenesis process in patients with systemic atherosclerosis (SA).Material and methods. In total, 46 SA patients (mean age 56,5±2,2 years) were divided into two groups, comparable by clinical and functional parameters. Group I (n=24) received standard therapy, while Group II (n=22) was administered standard therapy plus rosuvastatin (10 mg/d). In all participants, serum lipid profile, in vitro Cu-ion oxidation of serum and high-density lipoproteins (HDL), concentrations of 3-nitrotyrosine (3-NT), high-sensitive C-reactive protein (hs-CRP), and interleukin-6 (IL-6), activity of secretory phospholipase A2 Type IIA (secPHLA2-IIA), and VEGF and PIGF factor levels were measured.Results. Moderate doses of rosuvastatin significantly decreased serum and HDL oxidation — by 34% (р<0,01) and 37% (р<0,05), respectively. They also reduced the levels of 3-NT by 26% (р<0,05), hs-CRP — by 35% (р<0,05), and IL-6 — 26% (р<0,05). SecPHLA2-IIA activity decreased by 27% (р<0,05), VEGF level — by 28% (р<0,05), and PIGF level - by 43,5% (р<0,05).Conclusion. 3-NT and hs-CRP levels, together with secPHLA2-IIA activity, could be effective markers of systemic OS and endogenous inflammation in SA patients.